Comparative effectiveness of medical and surgical therapy on olfaction in chronic rhinosinusitis: a prospective, multi-institutional study - DeConde, Adam S. (2014)
BACKGROUND: Evidence comparing the impact of medical and surgical management of chronic rhinosinusitis on olfactory function is limited. This study evaluates olfactory outcomes in patients who failed initial medical management and elect either continued medical management or endoscopic sinus surgery (ESS) followed by medical management. METHODS: Adult subjects were prospectively enrolled into a non-randomized, multi-institutional cohort. Baseline characteristics, quality-of-life and objective clinical findings were collected along with two quality-of-life disease-specific measures, the Rhinosinusitis Disability Index (RSDI) and Sinonasal Outcome Test (SNOT-22). The primary outcome measure was the post-treatment change (≥6 months) in the Brief Smell Identification Test (B-SIT). Bivariate and multivariate analyses compared B-SIT changes by treatment type while controlling for baseline cofactors. RESULTS: Subjects (n=280) were enrolled between March, 2011 and May, 2013. Baseline B-SIT scores were comparable between medical and surgical treatment groups (8.8(3.2) vs 9.0(3.2); p=0.703). Subjects with baseline impaired olfaction (n=83; 29.6%) experienced mean B-SIT improvement in both the medical (n=17, 2.3(2.8), p=0.005) and surgical (n=66, 2.1(3.0), p<0.001) cohort. 38.6% of subjects with impaired olfaction return to normal olfaction at follow-up with no difference identified between treatment modalities (p=0.803). Multivariate analyses identified prior surgery as a predictor of less improvement regardless of treatment modality in patients with baseline impaired olfaction. Average changes in B-SIT scores were comparable between treatment groups (p>0.050). CONCLUSION: Subjects electing ESS experienced gains in olfaction comparable to subjects electing continued medical management. Further study with larger sample size and more sensitive measures of olfaction are needed to determine differences between treatment groups.